2023
DOI: 10.3390/diagnostics13030501
|View full text |Cite
|
Sign up to set email alerts
|

How Frequently Benign Uterine Myomas Appear Suspicious for Sarcoma as Assessed by Transvaginal Ultrasound?

Abstract: Background: Uterine myomas may resemble uterine sarcomas in some cases. However, the rate of benign myomas appearing as sarcomas at an ultrasound examination is not known. The objective of this study is to determine the percentage of benign myomas that appear suspicious for uterine sarcoma on ultrasound examination. This is a prospective observational multicenter study (June 2019–December 2021) comprising a consecutive series of patients with histologically proven uterine myoma after hysterectomy or myomectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Our ultrasound findings for uterine sarcoma are in line with those of previous publications 12,23,24 , which reported irregular tumor borders, cystic areas in the lesion (as a sign of central necrosis), non-uniform echogenicity, moderate-to-abundant intralesional vascularity and an absence of calcifications. Some studies have shown significant overlap in the sonographic features of benign and malignant myometrial lesions 24,25 , with up to 5% of benign leiomyomas being classified as suspicious for a sarcoma based on ultrasonography 25 . Uterine sarcomas tend to present with moderate-to-abundant intralesional vascularity.…”
Section: Discussionmentioning
confidence: 99%
“…Our ultrasound findings for uterine sarcoma are in line with those of previous publications 12,23,24 , which reported irregular tumor borders, cystic areas in the lesion (as a sign of central necrosis), non-uniform echogenicity, moderate-to-abundant intralesional vascularity and an absence of calcifications. Some studies have shown significant overlap in the sonographic features of benign and malignant myometrial lesions 24,25 , with up to 5% of benign leiomyomas being classified as suspicious for a sarcoma based on ultrasonography 25 . Uterine sarcomas tend to present with moderate-to-abundant intralesional vascularity.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine fibroids may resemble uterine sarcomas in some cases. In a recent published study, Cabezas et al [34] conclude that approximately 5% of benign uterine fibroids may exhibit sonographic suspicion of sarcoma based on Ludovisi et al [30] study. Although it is a small percentage, it is not negligible.…”
Section: Diagnosis Of Malignant Disease Prior To Surgery By Imagingmentioning
confidence: 99%